Blockchain technology in the supply chain - Rantanen, Roope (My University, 2022)
The purpose of this thesis is to explore blockchain technology and its usage and implications for the supply chain industry. Technology has had a significant impact on the supply chain management and blockchain is no different. Blockchain technology is being touted as a disruptor for managing supply chains and its possible applications are deemed considerable. One thing blockchain is very helpful with is driving cooperation within the supply chain. Supply chain integration and supply chain coordination can bring many benefits and blockchain can drive these very well. In today’s world where sustainability is more and more relevant, blockchain seems to bring much needed capabilities to different supply chains. This study aims to find how blockchain technology is used, what challenges blockchain has and, what are the implications of blockchain technology for the supply chain area. In this study, the data was gathered in expert interviews from two different organizations. Most of the interviewees were from a forestry company, so this study favors that viewpoint the most. Interviewees were all working in different roles, but all had some experience working with supply chains. The data was analyzed by thematically coding and developing a case description by comparing the results from theoretical background to the results from the interviews. According to the results, blockchain technology is and will be influential in the supply chain field. It is currently being used in many different supply chains all over the world. It is seen as a very useful technology in the forestry industry, especially in the product safety and product certification aspects. Many new implementations are happening and research around it is strong, even though the hype has gone down noticeably. The biggest challenges around blockchain technology are related to price, cooperation, and issues with the technology. The sustainability of blockchain is also a significant factor that is influencing its widespread implementation. The most significant effects of blockchain on the supply chain are increased transparency, traceability, and trust. Blockchain can also be a driver for cost reductions due to increased effectiveness as well as sustainability with enhanced analytical capabilities. Blockchain technology is still seeing some developments that may affect its future state and how widespread it will be used in supply chains.
Keywords: blockchain, supply chain, supply chain integration, supply chain collaboration, sustainable supply chain, challenges of blockchain, applications of blockchain, forestry industry